2019
DOI: 10.1190/geo2018-0627.1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent S-wave splitting parameters analysis: A case study from azimuthal PS data, Sanhu area of the Qaidam Basin, China

Abstract: The Sanhu area, which is located in the eastern Qaidam Basin in China and formed of low-amplitude anticlinal and lithologic traps, is a favorable area for biogas exploration. The fracture systems in this area are characterized in detail with the use of frequency-dependent S-wave splitting parameters, which are sensitive to the size of the fractures. The results indicate that the delay time between slow and fast S-waves decreases rapidly with increasing frequency between 5 and 30 Hz, and then it slowly decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Though this method can effectively distinguish the fractures in coal, the limitations lie in discriminating the fracture, as the type of fracture could not be identified. The fracture is sensitive to the frequency spectrum as the time delay between fast and slow shear waves changes with variation in frequency (Wang et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though this method can effectively distinguish the fractures in coal, the limitations lie in discriminating the fracture, as the type of fracture could not be identified. The fracture is sensitive to the frequency spectrum as the time delay between fast and slow shear waves changes with variation in frequency (Wang et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of azimuthal anisotropy from fractures in coal was shown by De et al (1998), Gray et al (2002) and Vetri et al (2003) using seismic data. Wang et al (2019) have shown that shear wave splitting parameters and fracture orientation extracted from the full azimuth multi-component seismic data are frequency dependent. Also, it was observed that the travel time delay of the split shear waves decreases with increasing frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the S waves generated by vertical source excitation have a wider frequency band than those generated by horizontal source excitation, providing higher resolution for imaging subsurface structures. The pure S‐wave exploration test carried out by China National Petroleum Corporation in the Sanhu area of Qinghai has obtained high‐quality pure S‐wave seismic data (Deng et al., 2022; Wang et al., 2019; Wu et al., 2018). S‐wave splitting analysis using pure S‐wave seismic data has also achieved good application results in the Sichuan Basin, China (Yang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%